Barriers and Changing Perceptions in Family Dietary Management of Hypertension: A Phenomenological Study in Primary Health Care - Aneng Yuningsih; Idhfi Marpatmawati; Yeli Yulianti (LPPM STIKes Muhammadiyah Ciamis, 2026)
Purpose: The purpose of this study is to explore family experiences in managing dietary practices among family members with hypertension. Methods:This study employed a qualitative approach with a descriptive phenomenological design. Participants were selected using purposive sampling, involving 12 families who had members diagnosed with hypertension in the working area of Kersanegara Primary Health Care, Tasikmalaya City. Data were collected through in-depth interviews using semi-structured interview guidelines and supported by field observations. Data analysis was conducted using thematic analysis based on phenomenological principles to identify key themes from participants’ experiences. Results: The findings revealed three main themes: (1) cultural barriers and preferences for salty foods, (2) lack of family support in implementing a low-salt diet, and (3) changes in family perceptions after receiving dietary education. In addition, families demonstrated improved understanding regarding appropriate salt intake for hypertensive patients after receiving education. Conclusions: Family dietary management in hypertension is influenced by cultural habits, family support, and health literacy. Therefore, community-based nursing interventions should emphasize family-centered education through integrated health programs and home visits to improve adherence to low-salt diets among hypertensive patients.